Uncovering factors associated with Malaysian Agribusiness Small Medium Enterprises (ASMEs) business sustainability: A qualitative approach - Nalini, Arumugam; Alageasan, Dhayalan; Fakhrul Anwar, Zainol; Bonaventure, Boniface (2017)
Agribusiness Small Medium Enterprises (ASMEs) could strengthen thelocal economy by creating job opportunities besides acting as the fundamental unit for larger firms. Even though ASMEs have comparative advantages and is important for thelocal economy.It is harder for them to sustain the industry compared to their larger counterparts, especially during their preliminary 5 years.Therefore, this study is aimed to determine factors of Malaysian ASMEs sustainability through a focus group discussion (FGD) with 11 local agribusiness practitioners followed by a qualitative analysis by using ATLAS.ti 7. As a result, four (4) factors, namely entrepreneurial passion and motivation, entrepreneurship skills, business management and business relations were found to influence Malaysian ASMEs business sustainability. The findings of this study would aid both policy makers and new agricultural entrepreneurs. However, a quantitative study involving more ASMEs owners is required to rectify and demonstrate the relationship between factors of ASMEs business sustainability.